Modelling farm-level adaptation of temperate, pasture-based dairy farms to climate change - Kalaugher, E.; Beukes, P.; Bornman, Janet; Clark, A.; Campbell, D. (Elsevier, 2017)
© 2017 Elsevier LtdProjections indicate that climate change may exacerbate existing challenges to the productivity of New Zealand dairy farming systems. To assess the importance of these projections and understand adaptation challenges at farm level, detailed farm-scale model simulations of climate change impacts were undertaken for six representative pasture-based dairy farms located in the major dairying regions of New Zealand. The analysis suggested that without adaptation, climate change is likely to have a negative impact in most of the study locations. However, the level and type of impact depends to a large degree on regional climate variability as well as on the management practices of each farm. Under current management, responses to projected climate changes ranged from no change to an 18% decrease in average annual pasture production. A number of modelled adaptations demonstrated the potential to reduce climate change impacts under current management. The modelling work, together with farmers' responses, showed the adaptations' potential to provide both benefits and management challenges across different regions and climate conditions. In particular, it highlighted the need for the results of farm systems modelling under climate change scenarios to be considered in the context of their specific and localised climatic and management challenges.